Post-traumatic effects in policing: perceptions, stigmas and help seeking behaviours. (2nd September 2016) - Heffren, Cole D.J.; Hausdorf, Peter A.
Abstract : This study explored the relationships between perceptions, stigmas and support with help seeking amongst police officers. A total of 421 web surveys were completed by constables from a large municipal police force in Canada. The most significant finding was the relationship between officers feeling comfortable disclosing distressing personal information and seeking help from others. Help was most commonly sought from respondents' friends (at work and outside) and family members. Respondents shared information with their direct supervisors only when there was a strong, reciprocal relationship between them. Implications for future research and practice for help seeking in police occupations are discussed.